Climate-smart villages and the hope of food secure households: Preliminary results from climate change adaptation and mitigation initiatives in the Nyando climate-smart villages - Kinyangi, James; Recha, John W.M.; Kimeli, Philip; Atakos, Vivian (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Preliminary results from climate change adaptation and mitigation initiatives in the Nyando climate-smart villages. Key messages include: shift in farming techniques reduces number of households eating one or no meals each day, households adopt three to five crop innovations and above, greatly expanding on-farm choices for resilient varieties, and resilient crossbreeds of small livestock better adapted to changing feed and water conditions in Nyando provide additional income.